2023
DOI: 10.1097/cji.0000000000000460
|View full text |Cite
|
Sign up to set email alerts
|

Development of Engineered CAR T Cells Targeting Tumor-Associated Glycoforms of MUC1 for the Treatment of Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is a common malignancy arising from the liver with limited 5-year survival. Thus, there is an urgency to explore new treatment methods. Chimeric antigen receptor T (CAR T) cell therapy is a very promising cancer treatment. Though, several groups have investigated CAR T cells targeting MUC1 in solid cancer models, Tn-MUC1-targeted CAR T cells have not yet to be reported in ICC. In this study, we confirmed Tn-MUC1 as a potential therapeutic target for ICC and demonstrated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Notably, although the functional mechanisms of mucin-positive cells may not be directly facilitated by mucins, mucin-directed immune therapy or chemotherapy still shows strong clinical application potential. Recently, MUC1 -directed chimeric antigen receptor (CAR) T cell therapies have shown promising killing effects both in-vitro and in-vivo [ 47 , 48 ]. Our data reveal attractive targets for immunotherapy, suggesting that anti- MUC4 , anti- MUC5AC , anti- MUC5B , anti- MUC13 or anti- MUC16 CAR T cells may also show promising treatment effects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, although the functional mechanisms of mucin-positive cells may not be directly facilitated by mucins, mucin-directed immune therapy or chemotherapy still shows strong clinical application potential. Recently, MUC1 -directed chimeric antigen receptor (CAR) T cell therapies have shown promising killing effects both in-vitro and in-vivo [ 47 , 48 ]. Our data reveal attractive targets for immunotherapy, suggesting that anti- MUC4 , anti- MUC5AC , anti- MUC5B , anti- MUC13 or anti- MUC16 CAR T cells may also show promising treatment effects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Both first and third-generation CAR T cells targeting MUC1 have been developed, which are able to specifically eliminate HCC cells with high MUC1 expression, while causing minimal damage to normal hepatic cells with low MUC1 expression levels [ 139 ]. A recent study has reported the use of Tn-MUC1-targeted CAR T cells in intrahepatic cholangiocarcinoma (ICC) [ 140 ]. Tn-MUC1 expression was associated with poor ICC prognosis [ 140 ].…”
Section: Car T Cell Therapy Targets For Hccmentioning
confidence: 99%
“…A recent study has reported the use of Tn-MUC1-targeted CAR T cells in intrahepatic cholangiocarcinoma (ICC) [ 140 ]. Tn-MUC1 expression was associated with poor ICC prognosis [ 140 ]. Moreover, Tn-MUC1-targeted CAR T cells could selectively eliminate Tn-MUC1-positive ICC cells, both in vitro and in vivo, while there was no effect in Tn-MUC1-negative ICC cells [ 140 ].…”
Section: Car T Cell Therapy Targets For Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…The study successfully demonstrated the specific cytotoxic activity of these CAR T against CCA cells [ 95 ]. Another study on antitumor efficacy in ICCA revealed the toxicity of Tn-MUC1 CAR T targeting glycosylated MUC1, both in vitro and in vivo [ 97 ]. In a recent study, fourth-generation A20-4G CAR T exhibited remarkable cytotoxicity against CCA cells expressing integrin integrin alphavbeta6/8 (αvβ6) [ 98 ].…”
Section: Current State Recent Advances and Challenges Of Immunotherap...mentioning
confidence: 99%